Case report: exome sequencing identified mutations in the LRP5 and LGR4 genes in a case of osteoporosis with recurrent fractures and extraskeletal manifestations - Mehta, Poonam; Sharma, Aakriti; Goswami, Anupam; Gupta, Sushil Kumar; Singhal, Vaibhav; Srivastava, Kinshuk Raj; Chattopadhyay, Naibedya; Singh, Rajender (Frontiers in Endocrinology, 2024)
Background: Genetic mutations have been reported in a number of bone disorders with or without extra-skeletal manifestations. The purpose of the present study was to investigate the genetic cause in a middle-aged woman with osteoporosis, recurrent fractures and extraskeletal manifestations. Methods: A 56-year-old Indian woman presented to the clinic with complaints of difficulty in walking, recurrent fractures, limb bending, progressive skeletal deformities, and poor overall health. At the age of 37, she had experienced severe anaemia with diarrhoea, significant weight loss, knuckle pigmentation, and a significant loss of scalp hair. She had received multiple blood transfusions and parenteral iron supplementation with normalization of haemoglobin. Subsequently, she had premature menopause at the age of 37. She died at the age of 61 due to liver failure. Exome sequencing followed by Sanger sequencing were undertaken to identify the potential pathogenic mutations. Results: Genetic investigation identified likely pathogenic mutations in the LRP5 and LGR4 genes. Out of the two mutations, the heterozygous mutation (c.1199C>T) in the LRP5 gene resulted in a non-synonymous substitution of alanine with valine at the 400th position, and the second mutation (c.1403A>C) in the LGR4 gene led to a non-synonymous substitution of tyrosine with serine at the 468th residue of the protein. The frequencies of the c.1199C>T (LRP5) substitution in the 1000 genomes and IndiGenomes databases are 0.0003 and 0.001, while the c.1403A>C (LGR4) substitution has not been reported in these databases. Various in silico prediction tools suggested LGR4 mutation to be pathogenic and LRP5 mutation to be likely pathogenic. Conclusion: Heterozygous mutations in the LRP5 and LGR4 genes had additive deteriorative effects on BMD, resulting in recurrent fractures and bone deformities, and extended the effect to extraskeletal sites, contributing to the poor overall health in this patient.